Severity of COVID-19 disease in pregnant and nonpregnant females of reproductive age group: A preliminary comparative study - Shariq Ahmed; Mohammad Shameem; Nazish Fatima; Uzma Tayyaba (Wolters Kluwer Medknow Publications, 2023)
Objectives: This study was conducted to compare the disease severity of COVID-19 in pregnant and nonpregnant females of reproductive age group and to evaluate the effect of COVID-19 on neonatal outcome. Materials and Methods: The present prospective observational study was conducted at a tertiary care center in northern India over a period of 6 months. Females of reproductive age group (15-44 years) that were admitted in COVID isolation ward with reverse transcription-polymerase chain reaction-positive COVID-19 disease were included in the study and followed till discharge. Results: Among the 60 females of reproductive age group, 41.67% (25) were pregnant and 58.34% (35) were nonpregnant. The median duration of hospitalization among pregnant and nonpregnant females was 9 and 8.5 days, respectively. The severity of infection among pregnant and nonpregnant females was as follows: asymptomatic + mild disease 96% (24) and 77.14% (27) and moderate + severe disease 4% (1) and 22.86% (8), respectively. There were no maternal mortalities. Forty percent (10) of pregnant females had lower segment cesarean section (LSCS) and 32% (8) had normal vaginal delivery. There were 8 preterm, 6 full-term, 3 early-term, and 1 late-term deliveries. Twelve newborns had normal birth weight, 4 were low birth weight (LBW), 1 was very LBW, and 2 intrauterine deaths IUD were reported. No case of neonatal death or neonatal asphyxia was reported. Conclusion: In comparison to nonpregnant women with COVID-19 pneumonia, the infected pregnant females had mild or no respiratory symptoms, and none developed severe respiratory compromise or required intensive care. Preterm delivery, LSCS, and LBW were common in COVID-19-infected females.